Effectiveness and safety of anti-PD-1 monotherapy or combination therapy in Chinese advanced gastric cancer: A real-world study - Li, Tao; Liu, Tingting; Zhao, Lei; Liu, Lu; Zheng, Xuan; Wang, Jinliang; Zhang, Fan; Hu, Yi (Frontiers in Oncology, 2023)
Purpose: Pembrolizumab and Nivolumab, have been approved for the treatment of locally advanced or metastatic gastric or gastroesophageal junction cancer (GC/GEJC) recently. Our study aimed to evaluate the effectiveness and safety of anti-PD-1-based treatment (monotherapy or combination therapy) in Chinese advanced or metastatic GC/GEJCs and populations with poor clinical conditions in a real-world setting and screen the advantaged population for immunotherapy. Methods: A retrospective cohort study was conducted and 54 patients during the time from May 31st, 2015 to May31st, 2021 were identified and included in our analysis, including 19 patients treated with anti-PD-1 monotherapy and 35 patients treated with anti-PD-1 combination therapy（24[68.6%] combined with chemotherapy, 4(11.4%) combined with target therapy, 5[14.3%] combined with chemotherapy and target therapy, 2[5.7%] combined with Ipilimumab）. Demographic and clinical information were evaluated. Clinical response, survival outcomes, and safety profile were measured. Results: In the overall cohort, the median overall survival (mOS) was 11.10 months (95%CI, 7.05-15.15), and the median progression-free survival (mPFS) was 3.93 months (95%CI, 2.47-5.39). 16.7% of patients reached clinical response, and 72.2% got disease control. Prolonged OS and PFS and increased clinical response were observed in the combination group compared with the monotherapy group, although statistical significance was not reached. In subgroups with live metastases or elevated baseline NLR levels, combination therapy outperformed anti-PD-1 alone in survival outcomes. Patients treated with anti-PD-1 monotherapy (n=5, 26.3%) had fewer TRAEs than those in the combination group (n=22, 62.9%). There were also fewer patients with TRAEs of grade 3 to 5 with monotherapy (n=2, 10.5%) than with combination therapy (n=7, 20.0%). Pneumonitis was the only potentially immune-related adverse event reported in our cohort, observed in 3 patients. Conclusions: Anti-PD-1-based monotherapy and combination therapy showed favorable survival outcomes and manageable safety profiles in advanced or metastatic GC/GEJCs. In clinical treatment, immunotherapy should be an indispensable choice in the treatment strategy for GC/GEJC.Patients with a heavy tumor burden and more metastatic sites might benefit more from combination therapy. Elderly patients and patients with more treatment lines or high ECOG performance scores might be more suitable for immune monotherapy, and some clinical benefits have been observed.